PENGARUH ENTREPRENEURIAL ORIENTATION TERHADAP FAMILY BUSINESS PERFORMANCE DENGAN ORGANIZATIONAL BUSINESS CULTURE DAN FAMILY INVOLVEMENT SEBAGAI VARIABEL MODERASI PADA UKM KOPRA HITAM DI KOTA PALU, SULAWESI TENGAH - David Sukardi Kodrat; Madina, Nur (International Journal of Economics, Business and Accounting Research (IJEBAR), 2025)
This study aims to examine the effect of entrepreneurial orientation on family business performance moderated by family involvement and organizational business culture. The variables used in the study are entrepreneurial orientation, family business performance, family involvement and organizational business culture. The population in this study were Black Copra family business SME entrepreneurs in Palu, Central Sulawesi. The sampling technique used was purposive sampling. The questionnaire was distributed through an offline questionnaire to respondents who were owners of Black Copra SME businesses in Palu, Central Sulawesi. This study obtained 200 samples that were suitable for analysis. The data were analyzed using Smart PLS software and using path analysis. The results of this study indicate that entrepreneurial orientation has an effect on family business performance moderated by family involvement and organization business culture of SMEs in the Black Copra family business in Palu, Central Sulawesi.